(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Perimenopause is the transition period from reproductive to non-reproductive phase. It usually begins with menstrual cycle irregularity and extends to one year after permanent cessation of menstruation. There is manifestation of varied physical, psychological and somatic symptoms. Menopause may be correlated to Rajakshaya. It usually occurs as part of the ageing process and is the period of transition from Pitta predominant middle age to vata predominant old age. Treatment in modern medicine includes hormone replacement therapy and use of anti-depressants etc. Acharyas mention Jara among Swabhavabala pravritta Vyadhi, and its management is to be done with drugs having Rasayana property. Here we present a 48-year-old lady who presented with complaints of hot flushes, severe sweating especially during night hours, reduced sleep, irritability, multiple joint pain, loss of interest in most daily activities and stress incontinence. Vayasthapana gana was administered as Ksheerapaka. Vayasthapana gana include ten drugs which are Rasayana, Medhya, Tridosha samana and possess anti-oxidant, free radical scavenging and anti-stress activity. Ksheera is Vata pitta samana, Rasayana, and Jeevaneeya. Vayasthapana gana ksheerapaka is given in the dose of 48ml twice daily one hour before food for thirty days. After treatment intensity of these symptoms were reduced. Follow up was done thirty days after stopping the medication, here also intensity of these symptoms remained less when compared to before treatment. Here we reviewed the probable role of Vayasthapana gana ksheerapaka in alleviating perimenopausal symptoms.